THE CORRELATION AMONG LEVEL OF KNOWLEDGE ABOUT ERGONOMIC POSITION AND LOW BACK PAIN COMPLAINTS IN INPATIENT NURSES - Tumpia, Novilia Velisya; Kadja, Lidesdianty Juwita Natalia; Candra, Yulius Dicky; Patrisia, Ineke; Pramusita, Santa Maya (Nursing Current: Jurnal Keperawatan, 2023)
Low Back Pain (LBP) is a collection of several clinical symptoms that are marked by pain or discomfort in the lower back, which may or may not extend to the legs. Incorrect ergonomics is the primary factor contributing to lower back pain (LBP) among nurses. The objective of this study was to establish a correlation between the extent of ergonomics knowledge and the occurrence of lower back pain (LBP) complaints among nurses who work with hospitalised patients. This study employed a correlational quantitative design, utilising a cross-sectional technique. The sample size for this study consisted of 158 nurses working in the inpatient unit of a private hospital in Indonesia. The sampling technique employed was a total sampling, resulting in a sample size of 158 nurses. The research employed questionnaires that were both valid and trustworthy. The questionnaires assessing knowledge of ergonomics were devised by Bunga et al. (2019), whilst the questionnaire pertaining to low back pain was formulated by Deria (2021). The findings of the Pearson chi-square statistical test indicated a p-value of 0.105, suggesting that there was no statistically significant association between the level of knowledge of ergonomics postures and complaints of low back pain among inpatient nurses. Inpatient nurses have the ability to discover and implement ergonomic postures in their regular tasks. Further research could be undertaken on the elements that can induce low back discomfort.